Current status of cardiac regenerative medicine; An update on point of view to cell therapy application - Mehdi Hassanpour; Nasser Aghamohamadzade; Omid Cheraghi; Morteza Heidarzadeh; Mohammad Nouri (Journal of Cardiovascular and Thoracic Research, 2020)
Cardiovascular diseases (CVDs) are the leading cause of death globally. Because of the economic and social burden of acute myocardial infarction and its chronic consequences in surviving patients, understanding the pathophysiology of myocardial infarction injury is a major priority for cardiovascular research. MI is defined as cardiomyocytes death caused by an ischemic that resulted from the apoptosis, necrosis, necroptosis, and autophagy. The phases of normal repair following MI including inflammatory, proliferation, and maturation. Normal repair is slow and inefficient generally so that other treatments are required. Because of difficulties, outcomes, and backwashes of traditional therapies including coronary artery bypass grafting, balloon angioplasty, heart transplantation, and artificial heart operations, the novel strategy in the treatment of MI, cell therapy, was newly emerged. In cell therapy, a new population of cells has created that substitute with damaged cells. Different types of stem cell and progenitor cells have been shown to improve cardiac function through various mechanisms, including the formation of new myocytes, endothelial cells, and vascular smooth muscle cells. Bone marrow- and/or adipose tissue-derived mesenchymal stem cells, embryonic stem cells, autologous skeletal myoblasts, induced pluripotent stem cells, endothelial progenitor cells, cardiac progenitor cells and cardiac pericytes considered as a source for cell therapy. In this study, we focused on the point of view of the cell sources.